Peruvian physicians’ religiousness and its influence on controversial bioethical decisions - Lavado Landeo, Lincoln (2018)
Objective: There is plenty of information about the influence of patients' religious beliefs to deal with their illnesses. However, little is known about the religious characteristics of physicians and how these influence their relationship with patients and treatment decision-making. This study aims to determine the religious patterns of the Peruvian medical population, and to know if these patterns have any correlation between physicians’ attitudes and bioethical decisions. Materials and methods: The non-randomized sample consisted of 200 people from three academic levels: medical students, residents, and master’s or doctoral students. Results: Seventy-six percent (76 %) of the physicians were believers, out of which 64 % were catholics. The religious level was determined considering four highly controversial ethical procedures: non-natural contraception, abortion, physician- assisted suicide and euthanasia. Physicians with high degree of religiousness (122 / 61 %) expressed their disagreement with the last three procedures, and physicians with high degree of intrinsic religiousness (45 / 22.5 %) disagreed with all them. Conclusions: Physicians’ religiousness influences their attitudes concerning medical treatments and bioethical decisions. There should be a method to prevent physicians’ religious commitment to influence their clinical decisions.